Analisis Framing Femisida Dalam Media Online Arus Utama Indonesia Berdasarkan Gender Penulis - Iik Nurul Fatimah; Dhita Amelia Kurnia; Nurain Nurain (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Mainstream media coverage of femicide is often positioned as an individual criminal event without linking it to the context of gender inequality. This study analyzes differences in the framing of femicide reporting in mainstream Indonesian online media based on the author's gender using Entman's (1993) framing model. Data were collected from five mainstream online media outlets and limited to articles published in the last five years. The sample was purposively selected and balanced into 10 articles, consisting of five by female authors and five by male authors (with no repeat authors), allowing for comparison of framing patterns. Analysis was conducted through qualitative coding of Entman's four elements: define problems, diagnose causes, moral judgments, and treatment recommendations. Results show that in both groups of authors, define problems were predominantly episodic, with an emphasis on the chronology of events, crime scene/forensic details, and the law enforcement process. Diagnose causes primarily highlighted relational/emotional triggers (e.g., arguments, jealousy, allegations of infidelity), while moral judgments tended to be implied through diction and source citations. Treatment recommendations were dominated by legal-procedural responses (investigation, detention, articles). A key difference emerged when the thematic framing was introduced through an institutional source (the National Commission on Violence Against Women), which classified the case as femicide and linked it to gender inequality. This finding indicates the role of news production routines and source selection in shaping framing, as well as the importance of strengthening the thematic context for more sensitive reporting on gender-based violence.